1998
DOI: 10.1111/j.1439-0507.1998.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV protease inhibitors influence the prevalence of oral candidosis in HIV‐infected patients: a 2‐year study

Abstract: The introduction of HIV protease inhibitors was accompanied by reduction in HIV-associated opportunistic infections. Therefore, we performed a retrospective study of HIV-infected patients to evaluate the effects of therapy with an HIV protease inhibitor (PI) on oral candidosis. This was of special interest, because an important virulence factor of Candida albicans is the secreted aspartic protease (SAP), which is assigned to the same class of aspartic proteases as HIV protease. Sixty-two patients were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 22 publications
(9 reference statements)
4
21
1
4
Order By: Relevance
“…Patients undergoing ART regimens displayed a reduction of clinically apparent oral candidiasis occurrence than patients not receiving ART, and this beneficial effect might be not completely due to a reconstitution of the immune status, but rather due to a direct effect on C. albicans. This hypothesis was confirmed in 1998 by Hoegl et al, who reported a case of a patient treated with antiretroviral drugs who recovered from fungal infection maintaining a low CD4 + T-cell counts 4 . Effects on oral candidiasis appeared in HIV patients treated with antiretroviral agents soon after therapy and before CD4 + cell recovery.…”
Section: Introductionsupporting
confidence: 63%
“…Patients undergoing ART regimens displayed a reduction of clinically apparent oral candidiasis occurrence than patients not receiving ART, and this beneficial effect might be not completely due to a reconstitution of the immune status, but rather due to a direct effect on C. albicans. This hypothesis was confirmed in 1998 by Hoegl et al, who reported a case of a patient treated with antiretroviral drugs who recovered from fungal infection maintaining a low CD4 + T-cell counts 4 . Effects on oral candidiasis appeared in HIV patients treated with antiretroviral agents soon after therapy and before CD4 + cell recovery.…”
Section: Introductionsupporting
confidence: 63%
“…These patients also tend to have a dramatically reduced incidence of oropharyngeal candidiasis (54,92,240). Since the Candida proteinases and the HIV proteinase are members of the same aspartyl proteinase family, these findings led to the hypothesis that HIV PIs may also act against Candida aspartyl proteinases in vivo and consequently prevent or reduce candidal infections directly (31,83,89). A spate of studies has followed to determine whether HIV PIs could inhibit C. albicans Sap proteins and whether they had any potential as therapeutic agents in the treatment of C. albicans infections.…”
Section: Modulation Of C Albicans Virulence By Aspartyl Proteinase Imentioning
confidence: 99%
“…On the other hand, Hoegh et al (44) suggested that inhibitors of HIV protease inhibited the prevalence of oral candidiasis in HIV-infected patients by their direct action on the secretion of SAPs by Candida spp., which are considered to belong to the same class of HIV aspartic proteases. Thus, the success of antiretroviral therapy could be attributed to several factors such as inhibition of one or more C. albicans virulence factors and recovery of the immunological state of infected patients (2,18,41,42,46,49,77).…”
Section: Oral Candidiasis Occurs In 90% Aids Patients Being the Mostmentioning
confidence: 99%
“…However, the role of humoral immunity in the defense against fungal infections, including those caused by Candida spp., is still highly controversial (44).…”
Section: Pathogenymentioning
confidence: 99%